Performance comparison of small-pixel CdZnTe radiation detectors with gold contacts formed by sputter and electroless deposition. (26th June 2017) - Bell, S.J.; Baker, M.A.; Duarte, D.D.; Schneider, A.; Seller, P.; Sellin, P.J.; Veale, M.C.; Wilson, M.D.
Abstract: Recent improvements in the growth of wide-bandgap semiconductors, such as cadmium zinc telluride (CdZnTe or CZT), has enabled spectroscopic X/ γ -ray imaging detectors to be developed. These detectors have applications covering homeland security, industrial analysis, space science and medical imaging. At the Rutherford Appleton Laboratory (RAL) a promising range of spectroscopic, position sensitive, small-pixel Cd(Zn)Te detectors have been developed. The challenge now is to improve the quality of metal contacts on CdZnTe in order to meet the demanding energy and spatial resolution requirements of these applications. The choice of metal deposition method and fabrication process are of fundamental importance. Presented is a comparison of two CdZnTe detectors with contacts formed by sputter and electroless deposition. The detectors were fabricated with a 74 × 74 array of 200 μ m pixels on a 250 μ m pitch and bump-bonded to the HEXITEC ASIC. The X/ γ -ray emissions from an 241 Am source were measured to form energy spectra for comparison. It was found that the detector with contacts formed by electroless deposition produced the best uniformity and energy resolution; the best pixel produced a FWHM of 560 eV at 59.54 keV and 50% of pixels produced a FWHM better than 1.7 keV . This compared with a FWHM of 1.5 keV for the best pixel and 50% of pixels better than 4.4 keV for the detector with sputtered contacts.